Improvement in strength and ductility of rotary friction welded Inconel 600 and stainless steel 316L with Cu interlayer. (April 2023) - Mishra, Neeraj Kumar; Shrivastava, Amber
Abstract: The objective of this work is to investigate the effect of Cu interlayer on the tensile strength and ductility of the rotary friction welded Inconel 600 and stainless steel 316 L joints, in welded and annealed conditions. Joints were made with and without Cu interlayer. The temperature and forces were recorded during rotary friction welding. The welded and annealed joints were subjected to tensile tests, microstructural analysis and fractography of fractured surfaces from tensile test samples. Microstructural observation at the joint interface revealed the elemental diffusion with minimal bulk intermixing of the base materials. The dynamic recrystallization led grain refinement was observed on the steel side and grain coarsening was noticed on the Inconel side, near the interface. A substantial severe plastic deformation zone was noticed in the interlayer region for the joint made with Cu interlayer. The strength and ductility of the joints with interlayer were 10.8% and 82.3% higher than the joints made without interlayer. Upon annealing, joint ductility improved by 14.2% and 8.8% for the joints made without and with interlayer, respectively.